Statin therapy and plasma free fatty acids: a systematic review and meta-analysis of controlled clinical trials - Sahebkar, Amirhossein; Simental-Mendía, Luis E; Pedone, Claudio; Ferretti, Gianna; Nachtigal, Petr; Bo, Simona; Derosa, Giuseppe; Maffioli, Pamela; Watts, Gerald F (British journal of clinical pharmacology, 2016)
AIM: The aim of this meta-analysis was to evaluate the effect of statin therapy on plasma FFA concentrations in a systematic review and meta-analysis of controlled clinical trials. METHODS: PubMed-Medline, SCOPUS, Web of Science and Google Scholar databases were searched (from inception to February 16 2015) to identify controlled trials evaluating the impact of statins on plasma FFA concentrations. A systematic assessment of bias in the included studies was performed using the Cochrane criteria. A random effects model and generic inverse variance method were used for quantitative data synthesis. Sensitivity analysis was conducted using the leave-one-out method. Random effects meta-regression was performed using unrestricted maximum likelihood method to evaluate the impact of potential moderators. RESULTS: Meta-analysis of data from 14 treatment arms indicated a significant reduction in plasma FFA concentrations following treatment with statins (weighted mean difference (WMD) -19.42%, 95% CI -23.19, --15.64, P < 0.001). Subgroup analysis confirmed the significance of the effect with both atorvastatin (WMD -20.56%, 95% CI -24.51, -16.61, P < 0.01) and simvastatin (WMD -18.05%, 95% CI -28.12, -7.99, P < 0.001). Changes in plasma FFA concentrations were independent of treatment duration (slope -0.10, 95% CI -0.30, 0.11, P = 0.354) and magnitude of reduction in plasma low density lipoprotein cholesterol concentrations (slope 0.55, 95% CI -0.17, 1.27, P = 0.133) by statins. CONCLUSIONS: The results of the present study suggest that statin therapy may lower plasma FFA concentrations. The cardiovascular and metabolic significance of this finding requires further investigation.
Keywords: Cholesterol, LDL; Cardiovascular Diseases; fatty acid; LDL-cholesterol; kyseliny mastné neesterifikované; Randomized Controlled Trials as Topic; Humans; randomizované kontrolované studie jako téma; Fatty Acids, Nonesterified; statiny; meta-analysis; dyslipidaemia; statins; kardiovaskulární nemoci; lidé; cholesterol; Hydroxymethylglutaryl-CoA Reductase Inhibitors